Participatory development of scaling plan as a part of low emission roadmap in rice production of Mekong River Delta - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
In December 2019, IRRI proposed a roadmap for adopting low-emission technologies in rice production including AWD-suitability maps for An Giang. This is currently a tentative working paper and will be published early 2020.